2020
DOI: 10.1253/circj.cj-19-0741
|View full text |Cite
|
Sign up to set email alerts
|

Changing Treatment Patterns in Patients With Venous Thromboembolism in Taiwan

Abstract: Background: In Asia, little information is available about contemporary real-world treatment patterns for venous thromboembolism (VTE). Methods and Results: Consecutive patients (n=11,414) from the Taiwan National Health Insurance Research Database with initial VTE and taking oral anticoagulants between May 1, 2014 and June 30, 2016 were included. The temporal trends of using oral anticoagulants and pharmacomechanical therapy during the study period were evaluated. The efficacy and safety of nonvitamin K antag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…To date, epidemiological studies on inpatients with VTE have been conducted in Denmark [ 15 ] and Japan [ 16 ], and the frequency of hospitalization for VTE in these countries has been determined. Regarding pharmaceutical treatment, previous studies have shown that DOAC use has increased in hospitalized patients with VTE while warfarin use has decreased [ 16 , 17 ]. However, these studies were mostly limited to inpatients, and the number of studies examining the epidemiology and treatment status in both inpatients and outpatients with VTE is limited.…”
Section: Introductionmentioning
confidence: 99%
“…To date, epidemiological studies on inpatients with VTE have been conducted in Denmark [ 15 ] and Japan [ 16 ], and the frequency of hospitalization for VTE in these countries has been determined. Regarding pharmaceutical treatment, previous studies have shown that DOAC use has increased in hospitalized patients with VTE while warfarin use has decreased [ 16 , 17 ]. However, these studies were mostly limited to inpatients, and the number of studies examining the epidemiology and treatment status in both inpatients and outpatients with VTE is limited.…”
Section: Introductionmentioning
confidence: 99%
“…The temporal trends of initial anticoagulant therapy in the group without active cancer indicated decreases for warfarin but increases for NOACs, a trend that was consistent with that reported in several previous studies. 21 22 23 24 In particular, rivaroxaban was the most prescribed NOAC across all studies, likely because of the rapid market access and preference toward a once-daily dosing regimen. 25 Sizeable proportions of noncancer patients who initiated PAC were observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, future studies with a longer follow-up are required to confirm the present findings. Third, although we included four DOACs, most patients (68.4%) received rivaroxaban, the first DOAC to be reimbursed by the Taiwan National Health Insurance in 2014 for VTE treatment [ 23 ]. The lesser use of other DOACs may have contributed to a potential bias in the event analysis.…”
Section: Discussionmentioning
confidence: 99%